Sophistry in the writings of Miguel De Unamuno: between politics and pedagogy - Astine OVSEPYAN (Hypothekai, 2023)
The article explores the legacy of Miguel de Unamuno, one of the most prominent Spanish intellectuals of the late 19th and ear-ly 20th centuries. Unamuno was known not only as a writer, but also as a philosopher, philologist, journalist, playwright, social activist, and educator with unique and innovative ideas for his time. The focus is on his statements about the activity of the sophists, literary and rhetorical sophistry, as well as the sophisti-cal concept of education in general. The key question is who the sophists were for Unamuno: wise men working for the benefit of the city or verbal craftsmen creating an educational danger for the citizens? In his essay “On Consequence and Sincerity”, where he discusses philosophical issues, Unamuno turns to the sphere of sophistical activity. He believed that there is a danger of be-coming dependent on some authority (sometimes false) both in education and politics. Students, like voters, are made to believe in someone else's truth, so is there not a sophist inside the teach-er and politician? Unamuno supports his point of view with an example of a man who hated politics but fell in love with the doctrines presented by his teacher. In his essay “The Exploitation of the Intelligent”, where Unamuno reflects on deceivers, he ar-gues that a sophist may win in foolish verbal tournaments but not in calm and thorough written discussions. Based on his corpus of philosophical and pedagogical essays, one can conclude that Unamuno had an ambiguous attitude towards the sophists and sophistical education. By saying that he always saw a sophist in the depths of every dogmatist and a dogmatist in the depths of every sophist, Unamuno asserts that if he had to choose, he would undoubtedly choose a sophist. It is difficult to classify Miguel de Unamuno as either an opponent or a supporter of the sophists; rather, he sympathizes with them, using their activities to construct his arguments, which sometimes resemble sophistic ones.